Expressão da proteína Bcl-2 como potencial biomarcador de progressão tumoral em carcinoma epidermóide oral - Có, Anna Clara Gregorio (2019)
Oral squamous cell carcinoma (OSCC) is the most common histological type of cancer of the oral cavity and presents a high mortality rate, about 50% of individuals diagnosed with OSCC evolve to death within a period of up to 5 years. Currently, there are no biomarkers able to predict prognosis and tumor progression features, in this way, the study of proteins responsible for apoptotic control and therefore involved in carcinogenesis has been in evidence. Thus, this study aims to evaluate the expression of Bcl-2 protein (B-cell lymphoma protein 2) as a prognostic biomarker and tumor progression in OSCC. We used clinical and follow-up data from 109 individuals with a conclusive diagnosis of OSCC. Histopathological analysis of gradation, patter of invasion, tumor lymphocytic infiltrate, perineural, vascular and lymphatic tumor invasion were evaluated on stained slides in Hematoxylin and Eosin. Fragments of tumor tissue, dysplasia and adjacent epithelium to the tumor were arranged in tissue microarrays and submitted to immunohistochemistry using anti-Bcl-2 antibody, clone 124. High Bcl-2 expression was observed in the tumor tissue, in relation to the adjacent epithelium to the tumor and dysplasia (p = 0.033), as well as on the tumor invasion front associated with the high degree of tumor lymphocytic infiltrate (p = 0.001). No difference was observed in Bcl-2 expression in tumor tissue when compared to clinical-pathological variables: tumor size, lymph node involvement, staging, age, gender, alcohol consumption and smoking. Additionally, Bcl-2 expression was not associated with prognosis in global and disease-free survival analyzes. We conclude that Bcl-2 protein may play an important role in indicating the malignant transformation potential of the oral epithelium in the tumor progression model used and may be a potential biomarker for the evolution of high-grade dysplasia for the CEO. However, in this study, Bcl-2 expression did not prove to be a good prognostic biomarker.